Exploring Digital Circular Economy Principles in Educational Institutions - Martinez, Santiago; Rodríguez, Juan Carlos; Lestari, Sri (Pandawan Sejahtera Indonesia, 2024)
The integration of digital circular economy (DCE) principles within educational institutions has gained increasing attention in recent years, as institutions strive to adopt sustainable and resource-efficient models. This paper explores the background of how DCE can be applied to enhance sustainability in the educational sector, focusing on reducing waste, optimizing resources, and fostering circular economic practices. The objective of this research is to analyze the effectiveness of DCE implementation in improving institutional sustainability and educational outcomes. The study employs a mixed-method approach, combining qualitative interviews with educational professionals and quantitative surveys to gather data on the adoption and impact of DCE principles. Results indicate that institutions which have integrated DCE strategies, such as digital resource sharing and the reuse of educational materials, have seen significant improvements in both resource management and educational performance. The findings suggest that the application of digital circular economy models contributes to reducing costs and enhancing the learning environment by promoting efficiency and sustainability. The conclusion highlights the potential of DCE as a transformative approach in the educational context, recommending further research on scaling these practices and their long-term impact on educational institutions.